Multi-pulse laser wakefield acceleration: a new route to efficient, high-repetition-rate plasma accelerators and high flux radiation sources - Hooker, S; Bartolini, R; Mangles, S; Tuennermann, A; Corner, L; Limpert, J; Seryi, A; Walczak, R (Institute of Physics Publishing, 2014)
Laser-driven plasma accelerators can generate accelerating gradients three orders of magnitude larger than radio-frequency accelerators and have achieved beam energies above 1 GeV in centimetre long stages. However, the pulse repetition rate and wall-plug efficiency of laser plasma accelerators is limited by the driving laser to less than approximately 1 Hz and 0.1% respectively. Here we investigate the prospects for exciting the plasma wave with trains of low-energy laser pulses rather than a single high-energy pulse. Resonantly exciting the wakefield in this way would enable the use of different technologies, such as fibre or thin-disc lasers, which are able to operate at multi-kilohertz pulse repetition rates and with wall-plug efficiencies two orders of magnitude higher than current laser systems. We outline the parameters of efficient, GeV-scale, 10 kHz plasma accelerators and show that they could drive compact x-ray sources with average photon fluxes comparable to those of third-generation light source but with significantly improved temporal resolution. Likewise free-electron laser (FEL) operation could be driven with comparable peak power but with significantly larger repetition rates than extant FELs.